Analisis Efisiensi Usahatani Kacang Hijau Varietas Fima 1 dan Varietas Lokal Melo Palue (Studi Kasus di Desa Magepanda Kecamatan Magepanda Kabupaten Sikka) - Julianus Jeksen; Mario Malado (Fakultas Pertanian, Universitas Nusa Nipa, 2025)
This study aimed to determine the amount of revenue, costs, and income received by farmers in mung bean farming of the Fima 1 variety (certified) and the local Melo Palue variety (non-certified), as well as the level of profit and efficiency obtained from farming these two mung bean varieties in Magepanda Village, Magepanda District, Sikka Regency. The results showed that the lowest income of respondent farmers using the Fima 1 mung bean variety was IDR 4,088,000, while the highest was IDR 21,702,000, with an average income of IDR 8,650,690. Meanwhile, the lowest income of respondent farmers using the local Melo Palue mung bean variety was IDR 1,350,000, and the highest was IDR 9,484,000, with an average income of IDR 2,532,640. The efficiency of mung bean farming using the Fima 1 variety had an R/C Ratio value of 24, meaning that every expenditure of IDR 1 generated a revenue of IDR 24. In contrast, mung bean farming using the local Melo Palue variety had an R/C Ratio value of 9, meaning that every expenditure of IDR 1 generated a revenue of IDR 9. Therefore, mung bean farming using both varieties was considered efficient and feasible to cultivate. However, farmers are advised to use certified seeds, namely the Fima 1 mung bean variety, because it provides higher income and greater efficiency compared to the local Melo Palue variety.